A study on clinicopathological spectrum of nodular hidradenoma - Padmanaban, Krishnan Govindaraman (International Journal of Research in Dermatology, 2022)
Nodular hidradenoma (NH) is an uncommon benign skin adnexal tumor that presents usually as solitary intradermal nodule. This study aims to discuss the various clinicopathological features of NH as it mimics other adnexal tumors, malignancies or metastasis particularly in uncommon sites. Twenty-four cases of histo-pathologically diagnosed NH during study period from 2016 to 2021were taken up for study. Their clinical, gross and microscopic findings were collected from records. Most tumors occurred in head in fifth decade. Cystic change was seen in majority of the cases. Tumor had dual population of cells with predominant clear cell component in five cases. Definitive cytological diagnosis was difficult requiring excision biopsy. Characteristic clinical and histological features help to distinguish NH from other potential mimickers NH need wide excision as they can recur and rarely transform in to malignancy.